A Noncontributory Pension Program for Older Persons in Yucatan, Mexico Implementing and Designing the Evaluation of the Program in Valladolid - Aguila, Emma (RAND Corporation, 2014)
This report describes Yucatan's efforts to design, implement, and evaluate a state government program to provide cash benefits to the elderly to improve their well-being. The report provides context and background for the program and describes its design and implementation. It also describes the design of the first evaluation of the program impact in Valladolid; the evaluation's findings will be presented in future publications.